Observational Study of Platelet Reactivity in Patients Presenting With ST-Segment Elevation Myocardial Infarction Due to Coronary Stent Thrombosis Undergoing Primary Percutaneous Coronary Intervention: Results From the European PREvention of Stent Thrombosis by an Interdisciplinary Global European Effort Registry - Godschalk, Thea C; Byrne, Robert A; Adriaenssens, Tom; Malik, Nikesh; Feldman, Laurent J; Guagliumi, Giulio; Alfonso, Fernando; Neumann, Franz-Josef; Trenk, Dietmar; Joner, Michael; Schulz, Christian; Steg, Philippe G; et al. (JACC. Cardiovascular interventions, 2017)
OBJECTIVES: High platelet reactivity (HPR) was studied in patients presenting with ST-segment elevation myocardial infarction (STEMI) due to stent thrombosis (ST) undergoing immediate percutaneous coronary intervention (PCI). BACKGROUND: HPR on P2Y12 inhibitors (HPR-ADP) is frequently observed in stable patients who have experienced ST. The HPR rates in patients presenting with ST for immediate PCI are unknown. METHODS: Consecutive patients presenting with definite ST were included in a multicenter ST registry. Platelet reactivity was measured before immediate PCI with the VerifyNow P2Y12 or Aspirin assay. RESULTS: Platelet reactivity was measured in 129 ST patients presenting with STEMI undergoing immediate PCI. HPR-ADP was observed in 76% of the patients, and HPR on aspirin (HPR-AA) was observed in 13% of the patients. HPR rates were similar in patients who were on maintenance P2Y12 inhibitor or aspirin since stent placement versus those without these medications. In addition, HPR-ADP was similar in patients loaded with a P2Y12 inhibitor shortly before immediate PCI versus those who were not. In contrast, HPR-AA trended to be lower in patients loaded with aspirin as compared with those not loaded. CONCLUSIONS: Approximately 3 out of 4 ST patients with STEMI undergoing immediate PCI had HPR-ADP, and 13% had HPR-AA. Whether patients were on maintenance antiplatelet therapy while developing ST or loaded with P2Y12 inhibitors shortly before undergoing immediate PCI had no influence on the HPR rates. This raises concerns that the majority of patients with ST have suboptimal platelet inhibition undergoing immediate PCI.
Keywords: senioři; trombocyty; infarkt myokardu s elevacemi ST úseků; platelet function tests; antagonisté purinergních receptorů P2Y; ST Elevation Myocardial Infarction; Platelet Function Tests; Adenosine Diphosphate; Purinergic P2Y Receptor Antagonists; Coronary Thrombosis; Europe; Time Factors; platelet aggregation; výsledek terapie; Evropa; Middle Aged; registrace; mužské pohlaví; aspirin; Receptors, Purinergic P2Y12; koronární trombóza; recidiva; léková rezistence; Registries; vyšetření funkce trombocytů; inhibitory agregace trombocytů; adenosindifosfát; P2Y(12) receptor antagonists; ženské pohlaví; Platelet Aggregation Inhibitors; purinergní receptory P2Y12; Humans; Recurrence; stent thrombosis; biologické markery; koronární angioplastika; stenty; lidé středního věku; časové faktory; Percutaneous Coronary Intervention; Stents; rizikové faktory; Drug Resistance; Biomarkers; Blood Platelets; Female; Aged; Risk Factors; Treatment Outcome; lidé; Male